Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kemampuan Berpikir Aras Tinggi Pada Teks Berita Kelas VIII - Perlita Herlina Siagian (BADAN PENERBIT STIEPARI PRESS, 2023)
This research is research and development or Research and Development (R&D) which aims to develop teaching materials for news texts through worksheets based on high-level thinking skills for grade VIII junior high school. The development model used is the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. This research limits development to the development stage. From the stages that have been carried out, the results obtained are that Class VIII students at GKPI Padang Bulan Private Middle School are very interested and need LKPD products in learning. This was obtained through questionnaire data analyzing students' needs for LKPD needs based on high-level thinking skills with a 100% presentation. Through the needs analysis data, the development of LKPD was designed and validated by material experts, design experts, and teacher responses. The results of the study show that